PENGARUH KEPEMILIKAN INSTITUSIONAL DAN DEWAN KOMISARIS INDEPENDEN TERHADAP PENGHINDARAN PAJAK DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI - Siti Khaerunnisa; Ayu Noorida Soerono (Pascasarjana Universitas Sultan Ageng Tirtayas, 2025)
This study aims to explain the impact of institutional ownership, an independent board of commissioners, earnings management, and tax avoidance. Institutional ownership, as an independent variable, was measured using the ratio of institutional share ownership to the total outstanding shares. The independent board of commissioners is used as a measure of the total board of commissioners. Tax avoidance, the dependent variable, was assessed using the ETR. In addition, earnings management acted as a mediating variable quantified through discretionary accruals. The study population includes all property and real estate companies listed on the IDX between 2017 and 2022. A purposive sampling method was employed, yielding 50 data samples for this study. Multiple regression analysis and the Sobel test were employed for data analysis, using SPSSv25 and an online Sobel calculator for processing. The results showed that institutional ownership has no effect on earnings management, and an independent board of commissioners has a negative effect on earnings management and no effect on tax avoidance. Institutional ownership and earnings management have a positive impact on tax avoidance. In addition, earnings management cannot mitigate institutional ownership concerning tax avoidance, but it can moderate the impact of independent boards of commissioners on tax avoidance.